Resolution of Chronic Inflammation, Restoration of Epigenetic Disturbances and Correction of Dysbiosis as an Adjunctive Approach to the Treatment of Atopic Dermatitis - Gregory Livshits; Alexander Kalinkovich (Cells)
Atopic dermatitis (AD) is a chronic inflammatory skin disease with multifactorial and unclear pathogenesis. Its development is characterized by two key elements: epigenetic dysregulation of molecular pathways involved in AD pathogenesis and disrupted skin and gut microbiota (dysbiosis) that jointly trigger and maintain chronic inflammation, a core AD characteristic. Current data suggest that failed inflammation resolution is the main pathogenic mechanism underlying AD development. Inflammation resolution is provided by specialized pro-resolving mediators (SPMs) derived from dietary polyunsaturated fatty acids acting through cognate receptors. SPM levels are reduced in AD patients. Administration of SPMs or their stable, small-molecule mimetics and receptor agonists, as well as supplementation with probiotics/prebiotics, demonstrate beneficial effects in AD animal models. Epidrugs, compounds capable of restoring disrupted epigenetic mechanisms associated with the disease, improve impaired skin barrier function in AD models. Based on these findings, we propose a novel, multilevel AD treatment strategy aimed at resolving chronic inflammation by application of SPM mimetics and receptor agonists, probiotics/prebiotics, and epi-drugs. This approach can be used in conjunction with current AD therapy, resulting in AD alleviation.